Sodium/(calcium + potassium) exchanger NCKX4 optimizes KLK4 activity in the enamel matrix microenvironment to regulate ECM modeling - Chan, Barry; Cheng, Ieong Cheng; Rozita, Jalali; Gorshteyn, Ida; Huang, Yulei; Shaffer, Ida; Chang, Chih; Li, Wu; Lytton, Jonathan; Den Besten, Pamela; Zhang, Yan (Frontiers in Physiology, 2023)
Enamel development is a process in which extracellular matrix (ECM) models from a soft proteinaceous matrix to the most mineralized tissue in vertebrates. Patients with mutant NCKX4, a gene encoding a K+-dependent Na+/Ca2+ - exchanger, develop a hypomineralized and hypomature enamel. How NCKX4 regulates enamel protein removal to achieve an almost protein-free enamel is unknown. We characterized the upregulation pattern of Nckx4 in the progressively differentiating enamel-forming ameloblasts by qPCR, and as well as confirmed NCKX4 protein to primarily localize at the apical surface of wild-type ruffle-ended maturation ameloblasts by immunostaining of the continuously growing mouse incisors, posing the entire developmental trajectory of enamel. In contrast to the normal mature enamel, where ECM proteins are hydrolyzed and removed, we found significant protein retention in the maturation stage of Nckx4-/- mouse enamel. The Nckx4-/- enamel held less Ca2+ and K+ but more Na+ than the Nckx4+/+ enamel did, as measured by EDX. The alternating acidic and neutral pH zones at the surface of mineralizing Nckx4+/+ enamel were replaced by a largely neutral pH matrix in the Nckx4-/- enamel. In situ zymography revealed a reduced kallikrein-related peptidase 4 (KLK4) activity in the Nckx4-/- enamel. We showed that KLK4 took on 90% of proteinase activity in the maturation stage of normal enamel, and that recombinant KLK4 as well as native mouse enamel native KLK4 both performed less effectively in a buffer with increased [Na+] and pH, conditions found in the Nckx4-/- developing enamel. This study, for the first time to our knowledge, provides evidence demonstrating the impaired in situ KLK4 activity in Nckx4-/- enamel and suggests a novel function of NCKX4 in facilitating KLK4-mediated hydrolysis and removal of ECM proteins, warranting the completion of enamel matrix modeling.